Characterization of large area flexible plastic solar cells based on conjugated polymer/fullerene composites - Desta Gebeyehu; F. Padinger; C. J. Brabec; T. Fromherz; J. C. Hummelen; N. S. Sariciftci (International Journal of Photoenergy)
The development of solar cells based on composites of organic conjugated semi-conducting polymers with fullerene derivatives can provide a new method in the exploitation of solar energy. Organic solar cells must fulfill the criteria of stability, efficiency and reduction of production costs to find new applications. Specially, the bulk donor-acceptor heterojunctions between conjugated polymers and fullerenes have been successfully utilized for photovoltaic devices with high carrier collection efficiency compared to the devices made from single components. In this work we present measurements of the photovoltaic response of bulk donor-acceptor heterojunction between the conjugated polymer (as a donor, D) poly(3- octylthiophene), P3OT and fullerenes, (as acceptor, A), deposited between indium tin oxide and aluminum electrodes. These devices are based on ultrafast, reversible, metastable photoinduced electron transfer and charge separation.